2003
DOI: 10.1093/toxsci/71.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Environmental Combustion Particles Cause Myocardial Injury in the Wistar Kyoto Rat

Abstract: Epidemiologists have associated particulate matter (PM) air pollution with cardiovascular morbidity and premature mortality worldwide. However, experimental evidence demonstrating causality and pathogenesis of particulate matter (PM)-induced cardiovascular damage has been insufficient. We hypothesized that protracted, repeated inhalation by rats of oil combustion-derived, fugitive emission PM (EPM), similar in metal composition to selected sources of urban air PM, causes exposure duration- and dose-dependent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 30 publications
4
47
1
4
Order By: Relevance
“…Some of these effects are observed even at low, near -ambient levels of PM, supporting the hypothesis that PM induces cardiac effects; however, the mechanisms remain poorly defi ned. We have shown that episodic subchronic but not shorter pulmonary exposure to residual oil fl y ash PM for 16 weeks increased myocardial cell damage and focal fi brosis and infl ammation in Wistar Kyoto rats (Kodavanti et al, 2003 ). Our studies have further reported cardiac molecular changes in gene expression following acute one -time high concentrations of zinc exposure, refl ecting a direct effect on the heart .…”
Section: Cardiac Pathobiological and Molecular Alterations Induced Bysupporting
confidence: 54%
“…Some of these effects are observed even at low, near -ambient levels of PM, supporting the hypothesis that PM induces cardiac effects; however, the mechanisms remain poorly defi ned. We have shown that episodic subchronic but not shorter pulmonary exposure to residual oil fl y ash PM for 16 weeks increased myocardial cell damage and focal fi brosis and infl ammation in Wistar Kyoto rats (Kodavanti et al, 2003 ). Our studies have further reported cardiac molecular changes in gene expression following acute one -time high concentrations of zinc exposure, refl ecting a direct effect on the heart .…”
Section: Cardiac Pathobiological and Molecular Alterations Induced Bysupporting
confidence: 54%
“…A statement released by the American Heart Association (Brook et al 2004), based on an extensive review of available evidence, concluded that exposure to particulate matter air pollution can contribute to an increased risk of acute fatality from cardiovascular events in humans. Moreover, it has recently been reported that inhalation exposure of Wistar Kyoto rats to particulate matter containing zinc resulted in myocardial degeneration (Kodavanti et al 2003). In a series of chronic studies of dioxins and dioxin-like compounds conducted by the National Toxicology Program (NTP) in female Sprague-Dawley rats, increased incidences of cardiomyopathy were observed in rats exposed to 2,3,7,, or the dioxinlike compound 3,3 0 4,4 0 ,5-pentachlorobiphenyl (PCB 126) (Jokinen et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Estas diferenças podem portando significar que não há necessariamente uma similaridade nos desfechos, e que o valor prognóstico da VFC que é demonstrado em diversas patologias humanas, ainda é prematuro para uso em roedores como um indicador de prognostico negativo ou toxicidade após exposições a poluentes ambientais (Rowan III et al, 2007). Conforme apontado por Kodavanti et al (2003) os estudos experimentais que avaliam os efeitos da exposição ao MP de origem veicular baseiam se principalmente em achados fisiológicos, muito pouco se avaliou quanto a histopatologia e bioquímica do tecido cardíaco e além disso há uma grande variabilidade quanto aos métodos e duração da exposição, composição do MP utilizado e espaço de tempo entre as exposições e avaliação dos desfechos (Vincent et al, 1997;Watkinson et al, 1998;Campen et al, 2001;Wellenius et al, 2002) dificultando comparações.…”
Section: Discussionunclassified